Guide to biometrics for large-scale systems technological, operational, and user-related factors - Ashbourn, Julian; SpringerLink (Online service). (London Springer, 2011)
Although there have been significant developments in the field of biometrics in recent years, much of the research in this area has focused upon the front-end technology. This unique Guide to Biometrics for Large-Scale Systems considers biometric technology in a broader light, integrating the concept more seamlessly into mainstream Information Technology, while also striving to understand the cultural attitudes and the societal impact of identity management. This approach represents a step-change in current thinking that may come to be viewed as a milestone in the development of biometric technology in which many established tenets are placed under considerable scrutiny. Topics and features: Summarizes the material covered at the beginning of every chapter, and provides chapter-ending review questions and discussion points Reviews identity verification in nature, and early historical interest in anatomical measurement, which form the foundations of the modern field of biometrics Provides an overview of biometric technology, presents a focus on biometric systems and true systems integration, examines the concept of identity management, and predicts future trends Investigates performance issues in biometric systems, the management and security of biometric data, and the impact of mobile devices on biometrics technology Explains the equivalence of performance across operational nodes and why this is so important, introducing the APEX system as an example of how this issue can be addressed Considers the legal, political and societal factors of biometric technology, in addition to user psychology and other human factors This highly practical reference/guidebook is an invaluable resource for program managers, application developers and consultants working in this area. Students interested in biometric technology will also find this a must-read. Julian Ashbourn is an experienced and successful author on topics ranging from computer science and identity management through to geoscience and the natural sciences in general. His publications include the Springer titles Practical Biometrics: From Aspiration to Implementation, BANTAM User Guide: Biometric and Token Technology Application Modeling Language and Geological Landscapes of Britain.
Introduction -- Biometrics Revisited -- Biometric Systems Defined -- Identity Management -- True Systems Integration -- Performance Issues -- Equivalence of Performance -- Aligning Biometrics with Data -- The Mobile World -- Human Factors -- The Politics -- The Future -- Epilogue.
Electronic reproduction.
Keywords: Biometric identification; Electronic books